2007
DOI: 10.1007/s10681-006-9253-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of anthracnose resistance genes Co-4 3 and Co-9 in common bean cultivar tlalnepantla 64 (PI 207262)

Abstract: Tlalnepantla 64 (PI 207262) is an important source of genes for resistance to common bean anthracnose, caused by Colletotrichum lindemuthianum. However, these genes have not been fully characterized. Inheritance studies using crosses involving PI 207262 show that two independent genes confer resistance to anthracnose. Allelism tests showed that the genes are located at distinct loci from the previously identified resistance genes Co-1, Co-2, Co-3, Co-5, Co-6, and Co-10. Also, no segregation was observed in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 17 publications
4
29
1
1
Order By: Relevance
“…It presents a wide range of resistance; however it does not confer resistance to race 65 [23,37,76]. Although, five duplicated genes associated with resistance to race 65 of C .…”
Section: Discussionmentioning
confidence: 99%
“…It presents a wide range of resistance; however it does not confer resistance to race 65 [23,37,76]. Although, five duplicated genes associated with resistance to race 65 of C .…”
Section: Discussionmentioning
confidence: 99%
“…The plants were incubated and maintained in a mist chamber (20–22°C, 100% relative humidity) for 7 days. After this period, each plant was scored visually for disease symptoms as described by Alzate‐Marin et al. (2007).…”
Section: Methodsmentioning
confidence: 99%
“…In turn, Group II consists of twelve isolates of race 65, the isolates of race 17, race 2, MAFF 305390, R23.19, Rec15, the subgroup with isolate 11 from the State of Santa Catarina belonging to race 65, and races 23, 31, 73 and 1096. Gonçalves-Vidigal and Kelly (2006) used an isolate of race 65 that overcame resistance in cultivar BAT93 that differed from the one used by Alzate-Marin et al (2007) for which BAT93 showed resistance. In the present study, two groups within race 65 were observed in the phylogenetic tree.…”
Section: Similarity and Dissimilarity Measuresmentioning
confidence: 99%